Long COVID/Post-COVID-19 Syndrome - A Review - Burooj, Ahmed; Al-Ali, Ruqia (Clinical and Research Journal in Internal Medicine, 2024)
The COVID-19 pandemic has posed significant challenges to global healthcare systems, leaving behind a myriad of unanswered questions and long-term consequences. One such consequence is the emergence of a clinical phenomenon known as Long COVID, characterized by persistent symptoms following an acute COVID-19 infection. The long-term ramifications of this condition remain largely unknown. In this review article, the aim is to explore the most common symptoms associated with Long COVID, shed light on the difficulties in diagnosing the condition, and provide recommendations for its management. By examining existing literature and clinical observations, we seek to enhance our understanding of Long COVID and contribute to the development of effective strategies for its diagnosis and treatment. We searched PUBMED and SCOPUS for relevant research published in the last few years with the keywords ‘Long COVID’, ‘Long Haulers’, ‘Post-COVID-19 syndrome’, ‘Chronic COVID’, ‘Post-acute COVID-19’ and narrowed down to the 37 most relevant studies. The following is a discussion and review of the findings from the aforementioned.